Prevalence of anti A and anti B titer among blood group O donors / Alia Maisarah Mohd Azli and Mazura Bahari - Mohd Azli, Alia Maisarah; Bahari, Mazura (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Blood group O is well known as universal donors. However, some of the antibodies from group O, which are anti A and anti B may able to cause hemolysis of recipient's red blood cells if it is presented in sufficient high titer. Therefore, this pilot study was conducted to determine the prevalence of anti A and anti B titer among the blood group O donors. This study was carried out on 30 test tubes of blood, originated from leftover samples. All the samples from blood group O donors had been chosen randomly. Anti A and anti B antibody titration using the conventional tube technique had been done. Pearson Chi-square and Fisher's Exact test was used to compare the association between titration value and types of antibodies. This study showed that the prevalence of anti A and anti B titer among blood group O donors is 90.0% at the titer lower than 128. The critical value of 'high-titer' is also at the titer lower than 128. The result showed that there is no significance association between titration value and types of antibodies (p > 0.05). In conclusion, the blood group O donors can be accepted as the universal donors and can be released as safe O when the titer is lower than 128.